Digital Media Impact on Sufi Practices: Issuing Online Ijāzas for Dhikr Litanies - Ahmad Rizki; Hasan Rusdi (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
In Sufism, traditional Sufi practices such as granting ijāzas require direct transmission from teacher to student. However, with the rapid expansion of digital media, the process of granting ijāzas has undergone significant changes. This article examines the influence of digital media on Sufi practices, particularly in the context of issuing ijāzas for dhikr litanies via digital platforms. This study employs digital ethnography to investigate online participant engagement to analyze the validity of ijāza transmission via online platforms, supported by hadith sciences and a triangulation approach. The findings show that the evolution of digital media has transformed the implementation of ijāzas for dhikr litanies from individual to collective transmission methods. However, the process of authorization also involves the transmission of blessings and spiritual knowledge, which requires close engagement through direct interaction, thus suggesting that the traditional teacher-student relationship cannot be achieved and sustained online. Contribution: This article offers an understanding of the impact and validity of ijāzas offered through digital media, compared to the traditional method of direct transmission from teacher to student.